(untitled) (Al-Qamar, 2021)
This research includes poetry, the position of Islam, and the relationship between them. The search for Islamic literature tells us that the use of good, optimistic, appropriate, soft, beautiful, spiritual, magical and magical words, as the Prophet (peace and blessings of Allaah be upon him) said: "It is also a statement of magic." And Lilloth lies. The best of it is the mention of God Almighty and His highest qualities, praise, glory, ability, strength and kindness to His slaves. Islam has enriched poetry and uttered it on the lips of some poets who did not know it before. Perhaps the rapid response to the new content has spread the argues and short pieces of one purpose, thus giving rise to forms of poetry that fit the spirit of the times. Islam has supported poetry and poetry has unified with Islam passion, thought and style. The poet had a social function. He was committed to himself and his nation to volunteer his feelings, thinking and expression to serve Islam. The Muslim poets, individually and tribal, raised the nation’s conscience and renounced injustice and oppression. And fled to the security and justice and equality has been composed of hearts and lived a life of interdependent and fought the enemies of Islam in order to preserve the entity of the Islamic nation.